2010
DOI: 10.1002/etc.106
|View full text |Cite
|
Sign up to set email alerts
|

Pyrethroid insecticide concentrations and toxicity in streambed sediments and loads in surface waters of the San Joaquin Valley, California, USA

Abstract: Pyrethroid insecticide use in California, USA, is growing, and there is a need to understand the fate of these compounds in the environment. Concentrations and toxicity were assessed in streambed sediment of the San Joaquin Valley of California, one of the most productive agricultural regions of the United States. Concentrations were also measured in the suspended sediment associated with irrigation or storm-water runoff, and mass loads during storms were calculated. Western valley streambed sediments were fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 21 publications
2
40
0
Order By: Relevance
“…Environmental concentrations up to 0.66 mg/L ESF have been reported in water samples (Brady et al, 2006;Forbes and Cold, 2005), and it is frequently found in sediments and organic matter in aquatic systems at concentrations that are toxic to aquatic organisms (Allinson et al, 2015;Domagalski et al, 2010;EFSA, 2014;Ensminger et al, 2011;Fairchild et al, 1992;Rasmussen et al, 2013;Weston et al, 2013). However, investigations linking biochemical to life-history effects on aquatic sediment-dwelling invertebrates exposed to pyrethroids are still needed.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Environmental concentrations up to 0.66 mg/L ESF have been reported in water samples (Brady et al, 2006;Forbes and Cold, 2005), and it is frequently found in sediments and organic matter in aquatic systems at concentrations that are toxic to aquatic organisms (Allinson et al, 2015;Domagalski et al, 2010;EFSA, 2014;Ensminger et al, 2011;Fairchild et al, 1992;Rasmussen et al, 2013;Weston et al, 2013). However, investigations linking biochemical to life-history effects on aquatic sediment-dwelling invertebrates exposed to pyrethroids are still needed.…”
Section: Introductionmentioning
confidence: 96%
“…This widespread application leads to the common detection of pyrethroids in sediments of streams and lakes (Domagalski et al, 2010;Kuivila et al, 2012;Weston et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Method detection limits were taken from the respective studies. LC50 values were compiled by Domagalski et al [29] from the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Median lethal concentration (LC50) values for sediment toxicity are usually reported on an OC-normalized basis. For example, Hyalella azteca 10-day LC50 values for pyrethroids are typically reported at 1% OC, as compiled by Domagalski et al [40]. To match the toxicity data, PRZM-predicted concentrations of pesticide in eroded sediment were normalized by OC1 defined in each scenario (Table 3).…”
Section: Resultsmentioning
confidence: 99%